2019
DOI: 10.1186/s12984-019-0565-1
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of people with spinal cord injury learning to walk using a powered exoskeleton

Abstract: Background Powered exoskeletons for over ground walking were designed to help people with neurological impairments to walk again. Extended training in powered exoskeletons has led to changes in walking and physiological functions. Few studies have considered the perspective of the participants. The users’ perspective is vital for adoption of assistive devices. We explored the expectations and experiences of persons with spinal cord injury, training with the ReWalk exoskeleton. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 39 publications
(51 reference statements)
1
68
0
Order By: Relevance
“…Based on the purpose and location of use, the potential of a wearable exoskeleton can be identified. The expected potential of an exoskeleton has previously been addressed in a qualitative study by Manns and colleagues 28 . They found that some participants expected the best potential for outdoor exoskeleton ambulation, whereas others expected better potential for functional indoor use during daily life activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the purpose and location of use, the potential of a wearable exoskeleton can be identified. The expected potential of an exoskeleton has previously been addressed in a qualitative study by Manns and colleagues 28 . They found that some participants expected the best potential for outdoor exoskeleton ambulation, whereas others expected better potential for functional indoor use during daily life activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They found that some participants expected the best potential for outdoor exoskeleton ambulation, whereas others expected better potential for functional indoor use during daily life activities (e.g. cooking while standing) 28 . Yet, only when participants have an exoskeleton at their disposal in the home and community setting, the full potential of an exoskeleton can be truly assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Although end-users' perspectives are essential in the design and development of assistive technology [12,13], there is a paucity of literature from both persons with disabilities and physiotherapists (PTs) perspectives [14,15]. Over the last decade end-user perspectives have primarily been studied in spinal cord injury (SCI) in which four studies used semi-structured interviews [16][17][18][19], and 3 studies used survey methods [20][21][22] with sample size ranging from 3 to 20 persons. However, these studies included both complete and incomplete SCI with most participants being non-ambulatory representing a very different end-user population compared to persons post-stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding actuation, the most frequent actuators are electric motors, probably due to the fact that they are easy to control and exhibit great precision with high specific power . In fact, in the study by Manns et al [68] nine out of eleven participants said that they would be willing to take the exoskeleton home if the cost of the device was not a factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in order to avoid falls and provide balance, individuals need supportive devices such as crutches, walkers and canes ( Figure 5B), which can limit the independence and mobility of the user, and may lead to shoulder pain [67]. In the study by Manns et al [68], which evaluated the perspective of the participants after training with the ReWalk exoskeleton, several participants emphasized the effort exerted with the arms while using the exoskeleton. From this review, we found that patients with SCI commonly ended up using a walker or crutches whereas post-stroke patients, due to their hemiparesis, used a cane on the unaffected side.…”
Section: Design and Structurementioning
confidence: 99%